Fetoception: fetus within a fetus: a rare case presentation in a neonate - Garg, Sandeep; Yenkar, Anurag; Agrawal, Sana (International Journal of Contemporary Pediatrics, 2025)
Fetus in fetu (FIF) is a rare congenital anomaly where a malformed parasitic twin is found within a living host. It is often confused with mature teratoma due to overlapping features, but the presence of organized fetal structures and vertebrae helps differentiate FIF. A female neonate born at 37 weeks of gestation presented with a large sacrococcygeal mass. Prenatal anomaly scans suggested a sacral mass, and postnatal imaging, including radiographs and MRI, indicated a teratoma-like lesion. Surgical resection was performed on day four of life. Pathological analysis revealed a mass partially covered with skin and containing well-organized fetal tissues, including limbs, intestinal loops, and other organs, with no evidence of malignancy. The presence of vertebrae confirmed the diagnosis of FIF. Complete surgical excision was achieved, and the infant recovered uneventfully. The baby remained stable throughout the post-operative period and was discharged on day 11. This case highlights the diagnostic and clinical challenges in distinguishing FIF from a mature teratoma. FIF typically presents with recognizable fetal parts and vertebrae, unlike teratomas, which lack organized structures. Accurate diagnosis and early surgical intervention are crucial to manage FIF and prevent complications. While FIF is benign, mature teratomas carry a risk of malignancy, emphasizing the need for comprehensive evaluation. Further studies are essential to refine diagnostic criteria and improve differentiation between these conditions.